Strategi Engagement Media Sosial pada Industri Layanan Antar Makanan Online di Indonesia: Studi Komparatif ShopeeFood, GrabFood dan GoFood - Desi Wahyuni; Elsa Faturahmah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
The rapid growth of online food delivery services in Indonesia has encouraged food delivery companies to utilize social media as a strategy for digital communication and consumer engagement. This study aims to analyze the social media engagement strategies implemented by ShopeeFood, GrabFood, and GoFood in building relationships with digital audiences. The research employed a descriptive qualitative approach using the documentary review method through social media observations conducted over 14 days, from November 26 to December 9, 2025. Data were collected through non-participant observation, digital documentation, screen recordings, and engagement tracking on Instagram, TikTok, YouTube, and X platforms. The findings show that ShopeeFood applies a hard-selling strategy based on promotions and discounts with a high posting intensity, resulting in rapid and broad engagement. GrabFood predominantly utilizes storytelling and soft-selling approaches through daily-life narratives and influencers to create emotional connections with consumers. Meanwhile, GoFood adopts situational and humorous communication strategies but demonstrates lower posting intensity and engagement compared to its competitors. This study reveals that social media engagement strategies in the online food delivery industry are not solely transaction-oriented but also emphasize the formation of symbolic and emotional relationships through digital storytelling. These findings indicate the importance of digital public relations communication in maintaining consumer attention and loyalty in the platform-based digital era.